Strongly rational expectations equilibria with endogenous acquisition of information - Gabriel Desgranges; Maik Heinemann (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2005)
This paper analyzes conditions for existence of a strongly rational expectations equilibrium (SREE) in models with private information, where the amount of private information is endogenously determined. It is shown that the conditions for existence of a SREE known from models with exogenously given private information do not change as long as it is impossible to use the information transmitted through market prices. In contrast, these conditions are too weak, when there is such learning from prices. It turns out that the properties of the function which describes the costs that are associated with the individual acquisition of information are important in this respect. In case of constant marginal costs, prices must be half as informative than private signals in order for a SREE to exist. An interpretation of this result that falls back on the famous Grossman–Stiglitz–Paradox is also given.
Keywords: D82; D83; 330; Eductive Learning; Private Information; Rational Expectations; Strongly Rational Expectations Equilibrium; Rationale Erwartung; Asymmetrische Information; Lernprozess; Theorie; Gleichgewicht